2021
DOI: 10.1111/jace.18122
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution and chemical stability of Nd‐doped Y3Fe5O12 waste forms synthesized in molten salt at a low temperature

Abstract: Shengtai Zhang and Baoliang Xu contributed equally to this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…REE elements of the REE-MA fraction (MA = Am, Cm) exist as trivalent ions, Ce can be partially in the form of Ce 4+ . To simulate actinides in matrices, lanthanides are used, and Ce, Th or U are introduced instead of Pu [ 47 , 70 , 71 ]. Due to close ionic radii [ 50 ], Ce 3+ simulates Pu 3+ , while Nd 3+ and Eu 3+ simulate Cm 3+ and Am 3+ .…”
Section: Zirconolite and Murataite As Matrices For The Immobilization...mentioning
confidence: 99%
“…REE elements of the REE-MA fraction (MA = Am, Cm) exist as trivalent ions, Ce can be partially in the form of Ce 4+ . To simulate actinides in matrices, lanthanides are used, and Ce, Th or U are introduced instead of Pu [ 47 , 70 , 71 ]. Due to close ionic radii [ 50 ], Ce 3+ simulates Pu 3+ , while Nd 3+ and Eu 3+ simulate Cm 3+ and Am 3+ .…”
Section: Zirconolite and Murataite As Matrices For The Immobilization...mentioning
confidence: 99%
“…According to previous research, 35,36 a rise in Nd content may also affect the evolution of the solid solution's physical phase. Figure 3 shows the phase evolution under different dosages.…”
Section: Phase Composition and Evolutionmentioning
confidence: 95%
“…Obviously, when the Nd substitution level was x + y = 2.4, the main phase was found to be perovskite while the second phase was garnet, and the zirconia phase gradually disappeared. Although the perovskite structure can also be used as solidified substrate, other researchers 35,36 have shown that the chemical stability of the perovskite structure is lower than that of the garnet structure. In addition, our previous study also showed that the presence of the perovskite phase can adversely affect the chemical stability of garnet solid solution.…”
Section: Phase Composition and Evolutionmentioning
confidence: 99%